2021
DOI: 10.1590/0102-77863620119
|View full text |Cite
|
Sign up to set email alerts
|

Hotter, Longer and More Frequent Heatwaves: An Observational Study for the Brazilian City of Campinas, SP

Abstract: Worldwide there is accumulated evidence of heatwave intensification due to climate change. Regional differences in the effects of heatwaves require local studies to implement public mitigation and adaptation strategies. This work analyzes and characterizes heatwaves’ occurrence for the city of Campinas, Brazil, through an observational study from 1956 to 2018. The definition of heatwaves adopted requires that the maximum and minimum daily temperatures be above the daily limits derived from climate normal 1961-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…The years 2014, 2015 and 2019 were very hot compared with the average in Brazil. During these years, HW events affected a large part of the Brazilian territory, mainly in the Southeast (Mendes et al, 2022; Oliveira et al, 2021) and South (Alves et al, 2016; Cardoso et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The years 2014, 2015 and 2019 were very hot compared with the average in Brazil. During these years, HW events affected a large part of the Brazilian territory, mainly in the Southeast (Mendes et al, 2022; Oliveira et al, 2021) and South (Alves et al, 2016; Cardoso et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al (2021) analysed HWs in Campinas, SP State and also found significant and positive trends toward increasing frequency and duration on annual and seasonal scales, except for winter. The authors found that the most prolonged, intense, and frequent events occurred in the last 20 years and that a significant change in trend occurred in the early 1980s.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…O estudo mostrou também concordância com as anomalias de temperatura do ar nas escalas regional, continental e global, fornecendo uma evidência científica válida e forte de que as mudanças climáticas ocorreram na cidade nos últimos 100 anos. Oliveira et al (2021) analisaram e caracterizaram a ocorrência de ondas de calor para o município de Campinas, décimo quarto mais populoso do Brasil e o terceiro mais populoso do estado de São Paulo, com o objetivo de investigar seu impacto na saúde. O período analisado foi de 1956 a 2018 e os resultados apontaram para uma mudança significativa na tendência de aumento de temperatura a partir da década de 1980, com eventos mais intensos, mais frequentes e mais prolongados nos últimos 20 anos, coincidindo com a tendência provocada pelo aquecimento global.…”
Section: Introductionunclassified